Pendapatan dan Produksi Potensial Usahatani Konservasi Lahan Pantai di Kabupaten Bantul - Widodo, Aris Slamet (Universitas Muhammadiyah Yogyakarta, 2015)
Coastal land management are expected not only serves as an erosion control (wind), but also serves to increase farmer’s incomes. This study aims to analyze the income and the potential production of conservation farming system on coastal land in Bantul. The survey was conducted in the village of Srigading and Gadingsari Bantul. Income and potential production of four main commodities, namely red onions, red peppers, eggplant, and sweet potatoes were analyzed using Technical Efficiency Effect Model. Results of the study showed that from 0.1 hectares of coastal land, the farmers obtain the highest revenue of red pepper, which amounted to Rp 3.9 million in the dry season 1 and Rp 2.5 in the dry season 2; followed by red onions income, amounted to Rp 2.1 million in the rainy season and Rp1.6 in the dry season; while eggplant provide the lowest income, which amounted to Rp 98 thousand in the rainy season. The estimation results of Cobb-Douglas Stochastic Frontier Model with MLE method showed an increase in the potential of onion in the rainy season by 7.4%; eggplant 11.4% and 10.2% sweet potato. In the dry season 1, there is an increase in onion production by 10.6%; red chili 4% and 5.6% sweet potato. While in the dry season 2, there is an increased production of red onion and eggplant by 4.1% at 6.1%.